2019
DOI: 10.3389/fmicb.2019.02950
|View full text |Cite
|
Sign up to set email alerts
|

Silicate Fertilizer Amendment Alters Fungal Communities and Accelerates Soil Organic Matter Decomposition

Abstract: Soil microorganisms play a crucial role in organic matter decomposition and nutrient cycling in cropping systems. Compared to bacteria, fungal community composition and the role of fungi in organic matter decomposition and nutrient cycling in agro-systems are, however, elusive. Silicon (Si) fertilization is essential to improve agronomic performance of rice. The effects of the Si fertilizer application on the soil fungal community composition and their contribution in soil organic matter (SOM) decomposition ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…With the changes in plant nutrient concentration by Si, an effect on plant litter and organic matter decomposition is possible. It was shown that leaf material from reed [ 394 , 395 ] and rice [ 348 , 396 ] with high Si concentration decomposed faster than a litter of conspecific plants with a lower Si concentration. However, Emsens et al [ 397 ] found no effect of plant material Si concentration on decay rate.…”
Section: Implications For Ecosystem Structure Functioning and Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the changes in plant nutrient concentration by Si, an effect on plant litter and organic matter decomposition is possible. It was shown that leaf material from reed [ 394 , 395 ] and rice [ 348 , 396 ] with high Si concentration decomposed faster than a litter of conspecific plants with a lower Si concentration. However, Emsens et al [ 397 ] found no effect of plant material Si concentration on decay rate.…”
Section: Implications For Ecosystem Structure Functioning and Servicesmentioning
confidence: 99%
“…Furthermore, it was shown that an increase of Si in soil pore water might also be able to mobilize carboxylic groups from soil organic matter particles, hence potentially additionally increasing litter decomposition [ 399 ]. Another potential explanation for how Si is accelerating organic matter respiration is by a change in soil microbial decomposer community, as shown for reed litter decay—where Si reduced the concentration of ergosterol as a measure of sporulating fungi [ 395 ]—and for rice litter—where the abundance of increase in saprotrophic fungi increased with increasing Si availability [ 396 ]. Hence, how Si is altering the soil microbial decomposer community is currently unclear, as the existing studies partially contradict each other.…”
Section: Implications For Ecosystem Structure Functioning and Servicesmentioning
confidence: 99%
“…The increased abundance of several genes related to the carbon cycle, nitrogen fixation, and heavy metal reclamation functions was associated with the silicate fertilization (Das et al, 2019a). The same group reported the alteration in the saprotrophic fungal communities and accelerated organic decomposition under the silicate fertilizer application (Das et al, 2019c). In another study, silicon fertilizer increased crop yield while decreasing the heavy metal content in multiple metals contaminated soil and modifying the structure and heterogeneity of the bacterial community associated with the metal-resistance (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have demonstrated that applying slag-based silicate fertilizer in agriculture has tremendous potential for improving rice productivity, plant disease resistance, and metal detoxification (Ning et al, 2014;Das et al, 2019b;Wang et al, 2020). At the microbiome level, recent studies have shown the positive effects of silicate fertilizer on bacteria and fungi populations (Das et al, 2019c;Wang et al, 2020). It has been revealed that several bacterial phyla were enriched and depleted while exposed to silicate fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, total soil enzyme activities remarkably increased, indicating an improvement of nutrient cycling in response to silicate fertilizer application in rice paddy grown on Asenriched soils. Silicon-fertilization to improve soil enzyme activities in arable and forest soil has been proved effective [18,19].…”
Section: Silicate Fertilization Increases Soil Enzyme Activities Invomentioning
confidence: 99%